Permanent Deformation Behavior of a Cement-Modified Base Course Material - Chummuneerat S. (2017)
© 2016 The Authors. Published by Elsevier B.V. One of the major failure modes in flexible pavements having thin asphalt surface associates with rutting or permanent deformation in a base course layer. Thus the material characterisation in term of permanent deformation is important for the mechanistic-empirical pavement design. This study investigated the permanent deformation behaviour of a modified granular material used for the base course layer. According to the Austroads definition, modified granular materials are granular materials stabilised by adding a small amount of stabilising binder such as bitumen, cement or pozzolanic material. The performance of the original materials is thus improved with regard to aspects such as strength, plasticity, and moisture susceptibility. However, the improvement of tensile strength is not one of the purposes of stabilisation. Hydrated cement treated crushed rock base (HCTCRB), which is stabilised with cement, was used for this study. HCTCRB is made by blending standard crushed rock base (CRB) with 2% cement (by mass of dry CRB) at the optimum amount of water. Then the fresh mixture is cured for specified hydration periods. Consequently, the hydrated mixture is returned to the mixer to break the cementitious bonds generating during the hydration reaction. This procedure aims to produce a cement-modified material whilst maintaining unbound base course characteristics. This study evaluated the effect of hydration period and moisture content on the permanent deformation of the material. The hydration periods of the test specimens varied from 7 to 28 days. The moisture contents ranged from 60% to 100% of OMC, by wetting and drying the specimen. It was found that the moisture content of samples significantly influenced the performance of HCTCRB. However, a consistent performance trend over various hydration periods was not conclusive.